EFFECT OF ULTRASOUND FREQUENCY VARIATIONS ON THE ANTIBACTERIAL ACTIVITY OF ACTINOMYCETES ISOLATES AGAINST Salmonella typhi - Kenza Anggita Vindasari; Meiskha Bahar; Fajriati Zulfa; Muttia Amalia (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2026)
Salmonella typhi is a negative Gram bacteria that causes typhoid fever and requires alternative therapeutic approaches due to increasing antibiotic resistance. Actinomycetes are known as producers of secondary metabolites with high, stable, and adaptive antibacterial activity; however, their effectiveness is strongly influenced by the extraction method of bioactive compounds. Ultrasound-Assisted Extraction (UAE) has the potential to enhance extraction efficiency through cavitation effects and frequency variation, which has not been widely explored. This study aimed to determine the effect of different UAE frequencies (30 kHz, 40 kHz, and 50 kHz) on the ability of Actinomycetes isolates to inhibit the growth of S. typhi. Extraction was performed using UAE at three different frequencies. Antibacterial activity was evaluated using the well diffusion method on Nutrient Agar medium. The diameter of inhibition zones was measured using a digital caliper and analyzed using One-Way ANOVA followed by Bonferroni post hoc test. The mean inhibition zone diameters at 30 kHz, 40 kHz, and 50 kHz were 4.42 mm, 4.00 mm, and 5.76 mm, respectively. Based on the Davis and Stout classification, the 30 kHz and 40 kHz treatments were categorized as weak (<5 mm), whereas 50 kHz was classified as moderate (5–10 mm). Statistical analysis indicated significant differences among treatment groups (p < 0.05). These differences affected the effectiveness of Actinomycetes  in inhibiting the growth of S. typhi. The 50 kHz frequency exhibited the highest antibacterial activity, with the largest inhibition zone diameter indicating optimal efficiency in the release of secondary metabolite compounds.